2016
DOI: 10.3389/fmicb.2016.00155
|View full text |Cite
|
Sign up to set email alerts
|

The S-layer Protein DR_2577 Binds Deinoxanthin and under Desiccation Conditions Protects against UV-Radiation in Deinococcus radiodurans

Abstract: Deinococcus radiodurans has the puzzling ability to withstand over a broad range of extreme conditions including high doses of ultraviolet radiation and deep desiccation. This bacterium is surrounded by a surface layer (S-layer) built of a regular repetition of several proteins, assembled to form a paracrystalline structure. Here we report that the deletion of a main constituent of this S-layer, the gene DR_2577, causes a decrease in the UVC resistance, especially in desiccated cells. Moreover, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 79 publications
3
76
0
1
Order By: Relevance
“…Two important reactive oxygen species (ROS) scavengers, KatE and SodA, had more than one succinylation site, which are highly expressed in D. radiodurans . SlpA, a major S‐layer protein essential for binding of the antioxidant carotenoid deinoxanthin, had two succinylation sites . Moreover, proteins involved in distinct DNA repair pathways were found to be succinylated.…”
Section: Resultsmentioning
confidence: 99%
“…Two important reactive oxygen species (ROS) scavengers, KatE and SodA, had more than one succinylation site, which are highly expressed in D. radiodurans . SlpA, a major S‐layer protein essential for binding of the antioxidant carotenoid deinoxanthin, had two succinylation sites . Moreover, proteins involved in distinct DNA repair pathways were found to be succinylated.…”
Section: Resultsmentioning
confidence: 99%
“…Using electron microscopy, Rothfuss et al [8] have identified five layers: (1) the inner membrane, (2) the peptidoglycan cell wall, (3) the interstitial layer, (4) Hpi and the backing layer, and (5) the carbohydrate coat. D. radiodurans envelope has an unusual structure and composition with the outermost surface of this formation is the "pink envelope" containing carbohydrates, proteins, carotenoid (deinoxanthin [7]), lipids, and most likely the outer membrane [8]. SlpA (DR_2577) and Hpi (DR_2508) are the most abundant components responsible for the envelope maintaining [35].…”
Section: Survey Of S-layer Proteins (Slps) In Deinococcus Radioduransmentioning
confidence: 99%
“…The SLH domain of SlpA was shown to bind deinococcal peptidoglycan-containing cell wall sacculi [45]. Indeed, it has [8], PilQ (DR_0774) as a component related with the S-layer [35] and the predicted association between: (i) SlpA and deinococcal peptidoglycan-containing cell wall [45], (ii) SlpA and Hpi [45], and (iii) SlpA and deinoxanthin [7]. The association of SlpA with peptidoglycan on one side and Hpi on the other localizes this protein in the "interstitial" layer of the deinoccocal cell wall [45].…”
Section: Survey Of S-layer Proteins (Slps) In Deinococcus Radioduransmentioning
confidence: 99%
See 1 more Smart Citation
“…Foi estimado que este ganho de eficiência contribuiu para uma economia de ao menos 100 milhões de dólares por ano em custos energéticos em estações de esqui canadenses (SKIRVIN et al, 2000). O uso apropriado de produtos assim foi considerado seguro nos âmbitos de proteção ambiental (GOODNOW et al, 1990;SKIRVIN et al, 2000) e de saúde humana (LAGRIFFOUL et al, 2010), ainda que alguns autores apontem possíveis impactos negativos à vegetação (RIXEN; STOECKLI; AMMANN, 2003) e a comunidades de fungos no solo (FIORE et al, 2008).…”
Section: Apêndice a -Aplicações Biotecnológicas Da Nucleação De Gelo unclassified